Derrida et Khatibi — Autour du monolinguisme de l’autre - Dominique Combe (Carnets)
During the Bâton-Rouge congress, presided over by Edouard Glissant, in 1992, Jacques Derrida responds to Abdelkébir Khatibi, quoting Amour bilingue. Khatibi, on many occasions, pays tribute to his friend Derrida, whom he regularly invites over to Rabat. Le Monolinguisme de l’autre, published in 1996, originated from this dialogue and is a reflection on the linguistic situation of the “Franco-Maghrebi”. Unlike Khatibi, Derrida, an Algerian Jew raised in a colonial school, with regard to the French language, “has only one language”, “and it is not his”.